2021
DOI: 10.3390/w13172444
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical Evolution of an Aquifer Regulated by Pyrite Oxidation and Organic Sediments

Abstract: Detailed full-scale groundwater monitoring was carried out over a period of nine years, sampling at selected points along the groundwater flow direction in its final stretch. This established the hydrogeochemical evolution along the flow of a natural system formed by a calcareous aquifer which discharges and then passes through a quaternary aquifer of lake origin which is rich in organic matter. This evolution is highly conditioned by the oxidation of pyrites that are abundant in both aquifers. In the first aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…TOC is a measure of organic matter content, which can be used as a parameter to evaluate water pollution (Lee et al, 2020). High TOC values imply lower dissolved oxygen (Al-Said et al, 2018), which further in uences chemical reactions in the water (Sanz et al, 2021). The results of this analysis showed that groundwater from the west and middle areas (W1-W6, except W2) had higher TOC values than those in the east area (W7-W10).…”
Section: Hydrogeochemical Analysesmentioning
confidence: 89%
“…TOC is a measure of organic matter content, which can be used as a parameter to evaluate water pollution (Lee et al, 2020). High TOC values imply lower dissolved oxygen (Al-Said et al, 2018), which further in uences chemical reactions in the water (Sanz et al, 2021). The results of this analysis showed that groundwater from the west and middle areas (W1-W6, except W2) had higher TOC values than those in the east area (W7-W10).…”
Section: Hydrogeochemical Analysesmentioning
confidence: 89%
“…When the δ value is greater than 0, it indicates that stable isotopes in groundwater are depleted. The δ values of D and 18 O are calculated as follows:…”
Section: Hydrogen and Oxygen Isotope Characteristics (1) Groundwater ...mentioning
confidence: 99%
“…The δD-δ 18 O relationship is plotted in Figure 8. The karst water sample points are all located at the lower right of the atmospheric precipitation line, indicating that although the main source is atmospheric precipitation, they are influenced by strong evaporation during precipitation and infiltration, which leads to isotopic enrichment.…”
Section: Hydrogen and Oxygen Isotope Characteristics (1) Groundwater ...mentioning
confidence: 99%
See 2 more Smart Citations